Cooperative learning in process dynamics & control course for Undergraduate Chemical Engineering Students - Khairiyah Mohd. Yusof, 1965-; Mimi Haryani Hassim; The Triennial AEESEAP Conference (7th : 2003 : Universiti Malaya, Kuala Lumpur) (Skudai : Universiti Teknologi Malaysia, 2003)
50